From Expectations to Experiences: Students’ Perceptions of Specifications Grading in Higher Education - Adriana Streifer; Michael Palmer; Jessica Taggart (International Journal for the Scholarship of Teaching and Learning)
Specifications grading is a form of alternative grading that emphasizes transparency, low stakes, student learning, and equity. It has attracted practitioners for its potential to enhance student motivation, and to remedy several challenges of traditional grading. Specifications grading has become increasingly popular, yet little is known about students' perceptions of and experiences with it. We examined students’ predicted and actual experiences of specifications grading in courses across several disciplines at a research-intensive, public university in the United States. Particular attention was paid to how students perceive specifications grading to influence their motivations to learn. Most students expressed positive attitudes toward specifications grading both before and after experiencing it. Qualitative responses indicate that facets of motivation, including choice, value, and expectations of success, were important factors shaping students’ perceptions. Based on these findings, we conclude with recommendations for practice for instructors who are interested in implementing specifications grading.